Penguasaan dan Pemanfaatan Wilayah Pesisir yang Didirikan Bangunan di Kelurahan Pasar Belakang Kecamatan Sibolga Kota: Control And Utilization of the Coastal Area Which Established in the Kelurahan Pasar Belakang Sibolga Kota - Rizki Ikhsan Siregar; Muhammad Yamin; Zaidar Zaidar (DOKTRINA: JOURNAL OF LAW, 2022)
In article 7 paragraph (1) letter t of the Sibolga Mayor Regulation Number 16 of 2018 concerning the Utilization of Coastal Areas and Coastal Borders in Sibolga City, it is stated that the coastal area and coastal border can be used for one of the other existing buildings and/or existing buildings. have permission. The problems include the legality and control of the use of coastal areas where buildings are built, the application of the Sibolga Mayor Regulation number 16 of 2018, and the application for registration of rights in coastal areas at the Sibolga Land Office. This type of research is an empirical juridical research with descriptive analysis. The results of the research The community building on the coastal border and above sea level does not have legality and official permission from the Sibolga City Government. There are no detailed and specific rules in these articles to be used as guidelines for the use of coastal areas related to border boundaries, procedures for obtaining permits from the Sibolga City government. The application for registration of rights in the coastal area of ​​ Kelurahan Pasar Belakang, Sibolga Kota District has not been processed because the Law has not provided more concrete arrangements, especially regarding the granting of types of settlement rights on the coastal border and on water marine.